The leadless pacemaker and cardiac nursing care. (2nd November 2020) - Fletcher, Lisa
Abstract: A leadless intracardiac transcatheter pacing system has been designed to overcome the need for a pacemaker pocket and transvenous lead. Currently, the leadless pacemaker only offers VVI/R pacing and cannot provide atrial pacing. Additional clinical data are required to enable comparison with transvenous devices. In order to prepare a patient for the procedure, nurses need to understand the rationale and treatment options, including risk factors to ensure that patient safety remains central to all care. This article reviews leadless pacemakers as a treatment option, explores the key aspects of nursing care and analyses the complications of these pacemakers.